THE ROLE OF HISTORY EDUCATION IN PROMOTING TOLERANCE AND MULTICULTURALISM IN SECONDARY SCHOOLS IN THE PHILIPPINES - Ana Mae M. Monteza (Satmata: Journal of Historical Education Studies, 2025)
This study investigates the role of history education in promoting tolerance and multiculturalism in Philippine secondary schools, with the aim of identifying how historical narratives, pedagogical strategies, and classroom interactions shape students’ understanding of cultural diversity. Using a qualitative case study approach, the research was conducted at Quezon City National High School and Davao City National High School, involving 30 participants through semi-structured interviews, classroom observations, and document analysis. The findings reveal that while the national curriculum offers limited representation of minority histories, teacher agency and localized instructional practices can significantly enhance multicultural learning. Classrooms that applied participatory methods—such as dialogue, comparative analysis, and community-based content—demonstrated higher levels of student engagement and empathy toward different cultural groups. A key novelty of this study lies in its integration of peace education, historical empathy, and multicultural pedagogy within a single analytical framework, providing a holistic understanding of how history can be taught to foster social cohesion. Additionally, the study contributes a comparative regional perspective by analyzing schools in both Luzon and Mindanao, offering insights into how geographic and cultural contexts affect inclusive teaching. The research concludes that history education can serve as a powerful tool for nurturing intercultural understanding, but only when delivered through inclusive content and reflective pedagogy. Therefore, meaningful reforms in curriculum design, teacher training, and policy implementation are essential to maximize its transformative potential in diverse learning environments.